MANUSKRIP AL-MUKARRAR FĪ MĀ TAWĀTARA MIN QIRĀĀTI AL-SAB’I WA TAḤRIR: Kajian Kodikologi dan Filologi - Hidayah, Fina Fitrohtul; Humam, Abdul Wadud Kasful (STAI AL-ANWAR SARANG, 2021)
This paper examines the text of the science of qirā`at entitled al-Mukarrar fī Mā Tawātara min Qirāati al-Sab'i wa Taḥrir with a focus on the physical aspects of the text, the text, and the analysis of the context surrounding the birth of the manuscript. This research is a type of qualitative research, with the approach of codicology, textology and history of horizontal history of Muhammad Arkoun. The results show that the condition of al-Mukarrar's manuscript is quite good, complete, and all of his writings can still be read clearly. The base of the manuscript is European paper with a PROPATRIA paper stamp, and a GR (Georgius Rex) match paper stamp. The year of copying is thought to be around the early 19th century. There is information that until the end of the 20th century there was not a single qirā`at book that was taught to students in the archipelago. However, the existence of the al-Mukarrar manuscript in the midst of the intellectual relationship between Nusantara scholars and the Middle East which is increasingly solidly built, and the massive writing tradition in various Islamic boarding schools, naturally explains that prior to the 20th century, there had been teaching and learning activities regarding the science of qirā`at, which in turn led to the need to copy manuscripts in handwritten form.